(3QSGdI aj cjajI GdYed HGdUajMI GdLGeYIs ((3WGgQ Hf UGdM Hf CMeO GdLRGFQi s)
(3ChdgG (B:s
(3GdMeO ddg JYGdi hcai hHYO agPg QSGdI eNJUQI ai cjajI GdYed HGdUajMI GdLGeYI GdHGH GdChd ai JSejI GdQShe GdehVhYI ai hLg GdUajMI s
(3BNQgG (B:s
(3hGVQH eG ai bWQ GdHFQ ef GdGPQY ai (B12 (3hGbSe GdeLJeY Ydi GdGeGe aeG NQL dc aGfbU efg eG Hjf HUQc Edi GdGQV ef GdGPQY aeG Hbi agh Yeb GdHFQ s
(3GdfSNI HgG MhGTs
(3cJHJ gPg GdeNWhWI HQSe GdTjN eMeO CafOi GdWfWGhis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdadcs